Aflatoxin tests in herbal products and its quantification: Latest updates - Victor Jeyaraj, Simon Vienoth; Loy, Mei Jun; Goh, Khang Wen; Lean, Yen Loong; Chan, Siok Yee; Ming, Long Chiau (Frontiers in Nutrition, 2022)
Aflatoxin is naturally occurring mycotoxins produced by fungi. The existence of aflatoxin in herbal medicines is a well-known issue. The detection of aflatoxin with good sensitivity and also that is reliable in complex matrices like herbs usually necessitates difficult processes and powerful detection instrument in preparation of sample. This study investigated the global occurrence of aflatoxin contamination herbal products. This article pivots on key breakthroughs in preparation of sample and its importance in analytical technology. Studies from published studies were screened to determine the general level of aflatoxin contamination. The countries involved were Malaysia, Indonesia, Kenya, Brazil, Nigeria, Thailand, South Africa and Morocco. This review also includes recent studies on the development and application of screening assays such as lateral flow immunoassays, enzyme-linked immunosorbent assays, aptamer-based lateral flow assays, and cytometric bead arrays, as well as traditional chromatographic techniques for aflatoxin qualification or quantitation. The current study looks at aflatoxin contamination of key herbal drug raw material, which are frequently used in the production of numerous herbal pharmaceuticals. Contamination of aflatoxin might occur in herbal products if the ingredients such as medicinal herbs and plants that are used in manufacturing of herbal products are not dried thoroughly or stored inappropriately after preparation.